Strategic Framework for Enhancing Green Customer Loyalty in the Bottled Mineral Water Industry in Indonesia - Ikhsani, Khilyatin; Riyadi , Slamet; Tampubolon, Liosten Rianna Roosida Ully (Transpublika Publisher, 2025)
Recent years have seen a paradigm shift in consumer behavior, with consumers increasingly paying attention to products with lower environmental impacts. This change influences consumers to prefer products and brands committed to green business practices. This study aims to bridge the knowledge gap in strategic management by strengthening green customer loyalty for green products within a specific business environment, particularly in the Java region, Indonesia. This research is descriptive quantitative and implemented as a cross-sectional study. The study is conducted at the individual level. For data analysis, this study applies Partial Least Squares Path Modeling (PLS-SEM), using Smart PLS version 3.2.6. The research population includes residents living on Java Island. The sample size was calculated using Slovin's formula, 400 respondents. The sampling method employed is non-probability sampling, specifically purposive sampling. The results showed that the factors directly influencing green customer satisfaction include green product quality, green branding, green advertising, and green value. Meanwhile, the factors affecting green customer loyalty consist of green product quality, green advertising, green value, and green customer satisfaction. Green customer satisfaction effectively mediates the relationship between green product quality and green customer loyalty.